Literature Review on the Maturity Level of Procurement Units (UKPBJ) within the Indonesian National Police (Polri) - Ruth Cahayanti Simanjuntak; Achmad Lutfi (Lembaga Bale Literasi, 2026)
This study aims to analyze the maturity level of the Goods and Services Procurement Unit (UKPBJ) within the Indonesian National Police (Polri) based on a literature review. The concept of UKPBJ maturity levels is rooted in the Capability Maturity Model (CMM) and Procurement Maturity Model (PMM) approaches, which emphasize the gradual development of an organization from administrative functions toward strategic functions oriented toward performance and value. The method used is a qualitative approach involving a literature review, through the search and analysis of various scientific sources, regulations, and previous research relevant to government goods and services procurement. The study’s findings indicate that, in general, the maturity level of UKPBJs in Indonesia remains at the proactive stage, characterized by standardized processes but not yet fully integrated strategically. The Indonesian National Police’s UKPBJ maturity level is influenced by the organization’s complex, hierarchical, and nationally distributed nature. Based on the analysis, the Polri’s UKPBJ has demonstrated relatively high achievements in institutional, human resources, process, and information system aspects, meeting most of the criteria for a center of excellence. However, there are significant weaknesses in the performance management aspect, which has not been optimally managed, thereby hindering data-driven performance evaluation and improvement processes. This study concludes that improving the maturity level of the UKPBJ within the Indonesian National Police requires strengthening performance management, process integration, and the continuous development of human resource capacity. Additionally, optimizing the use of information technology as a tool for strategic decision-making is a critical factor in driving the transformation of the UKPBJ into a professional, effective, and accountable procurement organization.